Optimalisasi Fitur Instagram untuk Meningkatkan Kinerja Engagement dan Retensi Pengguna - Fatwa Arriva; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
Instagram has become one of the most popular social media platforms with millions of active users every day. Increasing user engagement and retention is a challenge faced by many companies using this platform. This research aims to identify and optimize Instagram features that can improve user engagement and retention performance. This research adopts a quantitative approach to analyze Instagram usage. Data was collected through an online survey involving respondents from various demographic groups. Statistical analysis was carried out to identify the influence of Instagram features on user engagement and retention. A/B experiments are also conducted to test the effectiveness of certain feature changes in improving platform performance. The research results show that interactive features such as Stories and IGTV have a significant impact on increasing user engagement and retention. Optimizing interactive features on Instagram can substantially improve user engagement and retention performance. This research makes an important contribution in understanding the factors that influence user engagement and retention on social media platforms, especially Instagram, and provides practical recommendations for social media application developers